Detection of bone morphogenetic protein 2 within avian genome using PCR-based method - Teh, Richard; Abu, Jalila; Omar, Abdul Rahman; Kumaran, J. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Bone Morhogenetic Protein 2 was first discovered by Urist (1965) when he implanted the demineralized bone in rat muscle pouch which result in bone formation at the implantation site. The presence of BMP 2 protein was further confirmed by Sampath and Reddi (1981) when they discovered the removal of BMP 2 protein caused the matrix failed to induce new bone formation. On the other hand, new bone formation was observed with the presence of BMP 2. Ever since then, the effects of BMP 2 has been actively study and lots of clinical trial have been done using recombinant BMP 2 protein produce from mammalian host but not from avian. Thus, the aim of this study is to detect the presence of BMP 2 gene within the avian genome. In order to amplify the BMP2 gene from avian genome, a set of primer was design based on the Gallus gallus nucleotides sequnces from NCBI (Accession: NM_204358.1). The two primers designed for this study were; forward primer (BMP2F) 5’-ATGGTTGCCGCCACCCGCTC-3’ and reverse primer (BMP2R) 5’-TCAGCGGCACCCGCAGCCCT-3’. DNA from few types of avian species were extracted from the respectively species feathers followed Richard and Jayaraj (2010) protocol and further subjected to PCR screening. The annealing temperature for this particular set of primer was set at 71.9°C. The PCR results were then send for sequencing. As shown in Figure 1.0, the PCR results in 1% agarose gel (w/v), the expected PCR products size was 1179 bps but the PCR product only shown about 950 bps instead of 1179 bps. However the sequencing results of these PCR products shown up to 94% similarity, when blast against the BMP 2 gene from NCBI. Despite the PCR products size were lesser than the expected size but it should be able to function in avian system as clinical report from Sample et al. (2008) had proven that recombinant human BMP 2 in calcium phosphate matrix as a bone graft substitute can be used for treatment of a comminuted, open humeral fracture in a whooping crane. Whereby, the Homo sapiens BMP 2 gene sequence (Accession: NM_001200.2) only shown 79% of similarity when blast against the Gallus gallus BMP 2 gene sequence.